Clinical and genetic analyses of premature mitochondrial encephalopathy with epilepsia partialis continua caused by novel biallelic NARS2 mutations - Hu, Wenjing; Fang, Hongjun; Peng, Yu; Li, Li; Guo, Danni; Tang, Jingwen; Yi, Jurong; Liu, Qingqing; Qin, Wei; Wu, Liwen; Ning, Zeshu (Frontiers in Neuroscience, 2022)
Biallelic NARS2 mutations can cause various neurodegenerative diseases, leading to growth retardation, intractable epilepsy, and hearing loss in early infancy and further progressing to spastic paraplegia, neurodegeneration, and even death. NARS2 mutations are associated with mitochondrial dysfunction and cause combined oxidative phosphorylation deficiency 24 (COXPD24). Relatively few cases have been reported worldwide; therefore, the pathogenesis of COXPD24 is poorly understood. We studied two unrelated patients with COXPD24 with similar phenotypes who presented with intractable refractory epilepsia partialis continua, hearing loss, and growth retardation. One patient died from epilepsy. Three novel NARS2 variants (case 1: c.185T>C and c.251+2T>G; case 2: c.185T>C and c.509T>G) were detected with whole-exome sequencing. c.251+2T>G is located at the donor splicing site in the non-coding sequence of the gene. The minigene experiment further verified that c.251+2T>G caused variable splicing abnormalities and produced truncated proteins. Molecular dynamics studies showed that c.185T>C and c.509T>G reduced the binding free energy of the NARS2 protein dimer. The literature review revealed fewer than 30 NARS2 variants. These findings improved our understanding of the disease phenotype and the variation spectrum and revealed the potential pathogenic mechanism of non-coding sequence mutations in COXPD24.